2009
DOI: 10.1007/s11064-009-9958-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Astrocytes the Missing Link Between Lack of Brain Aspartoacylase Activity and the Spongiform Leukodystrophy in Canavan Disease?

Abstract: Canavan disease (CD) is a genetic degenerative brain disorder associated with mutations of the gene encoding aspartoacylase (ASPA). In humans, the CD syndrome is marked by early onset, hydrocephalus, macroencephaly, psychomotor retardation, and spongiform myelin sheath vacuolization with progressive leukodystrophy. Metabolic hallmarks of the disease include elevated N-acetylaspartate (NAA) levels in brain, plasma and CSF, along with daily excretion of large amounts of NAA and its anabolic metabolite, N-acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Nevertheless, in accordance with the molecular water pump theory that NAA functions as an osmolyte, it was hypothesized that astrocytes play a role in CD via increased N-acetylaspartylglutamate (NAAG) and its interaction with astrocytic glutamate receptors and subsequent extracellular breakdown of NAAG and liberation of NAA, leading to osmotic shifts and intracerebral water accumulation (40). Following the paradigm of oligodendroglial ASPA, gene replacement therapy for CD has focused on ASPA restoration in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in accordance with the molecular water pump theory that NAA functions as an osmolyte, it was hypothesized that astrocytes play a role in CD via increased N-acetylaspartylglutamate (NAAG) and its interaction with astrocytic glutamate receptors and subsequent extracellular breakdown of NAAG and liberation of NAA, leading to osmotic shifts and intracerebral water accumulation (40). Following the paradigm of oligodendroglial ASPA, gene replacement therapy for CD has focused on ASPA restoration in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that defective survival and differentiation of immature oligodendrocytes may also be implicated in CD ( 108 ). Furthermore, the toxic effects of NAA in myelin vacuolization should not be neglected ( 109 ).…”
Section: Fatty Acid and Plasmalogen Disordersmentioning
confidence: 99%
“…Although the intracerebral NAA accumulation and dysmyelination appear to be the major regulators of the disease's progress and phenotype, experimental evidence 7 GRM3 and NAAG-peptidase are actually a complex reported to appear particularly in the white matter astrocytic cells (Baslow, 2008;Baslow and Guilfoyle, 2009;Fotuhi et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested to prevent NAA release from neurons or increase expulsion from the CNS by affecting blood-brain barrier (BBB) permeability ). An alternative mechanism that could be targeted is inhibition of the NAA synthetic pathways (Baslow and Guilfoyle, 2009). The latter could either be accomplished by competitive or irreversible inhibition of aspartate N-acetyltransferase (AspNAT; the enzyme that synthesises NAA from Asp and Acetyl-CoA) (Figure 1.c) or by inhibiting NAAGpeptidase in order to prevent NAA synthesis from NAAG hydrolysis; the latter is further discussed below.…”
Section: Reduction Of Cns Naa Levelsmentioning
confidence: 99%
See 1 more Smart Citation